Preparing ethical review systems for emergencies: next steps - Wright, K.; Aagaard, N.; Atuire, C.; et al. (BMC Medical Ethics, 2023)
Ethical review systems need to build on their experiences of COVID-19 research to enhance their preparedness for future pandemics. Recommendations from representatives from over twenty countries include: improving relationships across the research ecosystem; demonstrating willingness to reform and adapt systems and processes; and making the case robustly for better resourcing.
Research Artcle
Keywords: Ethical preparedness; research ethics; ethical review